Cytotoxic activity of extracts from Tecoma species and isolated lignans - Adriana Cotta Cardoso Reis; Breno Mello Silva; José Dias Souza Filho; Guilherme Rocha Pereira; Geraldo Célio Brandão (Universidade de São Paulo, 2023)
Abstract A phytochemical study of Tecoma genus (Bignoniaceae) was accomplished by antitumor activity of ethanolic extracts. Species of this genus are composed of small shrubs often used as ornamental plants. The Tecoma stans species is used in folk medicine for different purposes. Recent work shows in vitro anticancer activity against human breast cancer. The ethanolic extracts from leaves and trunks of Tecoma casneifolia, T. garrocha, T. stans var. angustata and T. stans var. stans were tested in vitro. The assays used were against line tumor cells by the MTT method and the most active extracts were further studied. In this way, the ethanolic extract from T. stans var. stans trunks presented the higher cytotoxicity against the tumor cell lines studied (CC50 0.02 to 0.55 µg/ml) when compared to the other extracts tested (CC50 0.08 to 200.0 µg/ml). Accordingly, this extract was selected for chromatographic fractionation from which five known lignans were isolated. Further, paulownin, paulownin acetate, sesamin, olivil and cycloolivil were identified using 13C and 1H NMR, IR, UV and spectroscopy and spectrometric MS techniques. These isolated compounds were tested and exhibited CC50 ranging from 13.01 to100.0 µg/ml which is superior to the ethanolic extract of trunk of T. stans.